Posibles sistemas de registro y contabilidad en el Neolítico del Próximo Oriente - Rubio de Miguel, I. (ISIMU, 2016)
Tokens found in the Middle East settlements and studied by Denise Schmandt-Besserat years ago in several museum collections were identified as calculi. The appear from IXth millennium B.C. to urban period. Afterwards, new findings corroborated this hypothesis, although it was controversial. Here neolithic tokens are analysed and, taking into account seals and storage devices, the existence of some social complexity growing gradually is argued, as well as the validity of D. Schmandt-Besserat interpretation of tokens.